Vitruvius Without Text - Tavares, André (2022)
Vitruvius’s “De architectura,” written in the first century BCE, has been revered as the first treatise on architectural theory. Since its resurrection during the Renaissance, its enigmatic text has been adjusted, refined, and redefined in subsequent iterations. The book at hand bypasses exegeses of the text to focus on the material history of the printed editions disseminated throughout Europe. It surveys over a hundred editions of Vitruvius from 1486 to the present, tracing the power of the printed page in establishing the Roman author as an authority. Focusing on the impact of the physical objects that embody the Vitruvian canon highlights how book history and architectural history cross paths and how a symbiotic relationship between the printed and the built emerges. The resulting picture is that of a zigzagging thread between practice and theory, an elusive network of fruitful carelessness in architecture.